An Economic Analysis of Marine Cage Culture in Peninsular Malaysia - Salim, Kamaruzaman (1988)
Marine fish cage culture is a new emerging aquaculture enterprise in Malaysia. Recently, it has been selected as one of the culture methods to be promoted in the Malaysian Aqua cultural Development Programme. However, the present productivity of this culture system seems low compared to its potential. Therefore.the objective of this studs to find ways to increase. productivity of marine cage culture which could reduce per unit cost of production, leading to improved profit. This study explores the issue of relative economic efficiency (which includes technical and price efficiency ) between the family unit and commercial farms, and the issue of farmers' production behavior. The profit function approach is used to achieve the objectives. The normalized restricted translog profit function is specified as a function of three normalized prices of variable inputs (ie. fingerlings, feed and labour), two fixed inputs ( ie. cage volume and experience ) and a dummy variable to distinguish the family-unit and commercial farm groups. The result indicates that all sampled farms are not able to maximise their short-term profit. This is because there is a significant difference in relative economic efficiency between family-unit and commercial farm groups. It is also revealed that the family-unit farmers are not able to maximise their short-term profit. This result reflects that they are not price efficient because the ir efficiency in utilizing their feed resources. As a result, they are not able to equate marginal product value of the feed to its price. The reason is that they are not able to adopt fully t h e new culture technology. On the other hand, the commercial farmers maximize their profit and use their resources efficiently. It is also found that the commercial farms possess a superior technical efficiency as compared to the family-unit farms. Besides, the commercial marine cage culture production does not follow constant return stocale . In addition, the translog functional form is found out to be more appropriate than Cobb-Douglas form for data analysed. The productivity and profitability of the family-unit marine cage culture can be increased through improving price and technical efficiency. While, the productivity and prof it can only be increased through enhancing technical efficiency for the commercial farming. As such, it is recommended that marine cage farming within the commercial size should be encouraged in Peninsular Malaysia.